Habitação social e centro de atividades para a terceira idade - Molina, Mayara Coghi (2015)
The growth of Brazilian older people population is a process that has been developing in recent decades within the country, propelling changes in the conception of Third Age and of these individuals special necessities. Mainly in urban accessibility and housing concerns, it is noticed that the adequacy necessity is noticed by both public and private sectors, being this last one the main investor in real estate developments focused in this parcel of society. Even though the legislation for the rights of older persons, for example the Elderly Statute, establishes a non-seclusion model of senior housing that promotes active engagement in community, social and family lives, Brazilian most common senior housing model is a private institution or long-term care facility, where residents' freedom rights are neglected and quality of life rates are low, affecting their physical and emotional wellbeing. In this context, the present research aims to review existing literature and analyse architectural references, in order to propose an architecture design which promotes quality of life and reinsertion of older people into society, taking into consideration practical and emotional aspects, such as environmental quality and personhood.